Fischer–Tropsch Synthesis: Morphology, Phase Transformation, and Carbon‐Layer Growth of Iron‐Based Catalysts. Issue 7 (4th June 2014) - Pendyala, Venkat Ramana Rao; Graham, Uschi M.; Jacobs, Gary; Hamdeh, Hussein H.; Davis, Burtron H.
Abstract The morphological, phase transformations and carbon‐layer growth for unpromoted and K‐promoted iron catalysts were investigated over time during Fischer–Tropsch synthesis. Catalysts were activated in CO for 24 h, which transformed hematite into a mixture containing 93 % iron carbide and 7 % magnetite for the unpromoted catalyst and 81 % iron carbide and 19 % magnetite for the K‐promoted catalyst. Initially, the activated catalysts had high CO conversions (≈85 %); however, the conversions decreased to approximately 30 % after approximately 280 h of synthesis time. For the unpromoted catalyst, the amount of iron carbide gradually decreased over time while the corresponding magnetite phase increased. However, for the K‐promoted one, only one iron carbide phase (χ‐Fe5C2) gradually decreased, while the other (<alternatives> <![CDATA[ε ]]> <inline-graphic xlink:href="ark:/27927/pghr2bw5j4" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>‐Fe2.2C) phase steadily increased and magnetite remained unchanged. TEM analyses revealed that for the K‐promoted catalyst, carbon deposition increased over time, unlike that of the unpromoted catalyst.